Child Protective Services Referral in a Cleft Lip and/or Palate Population: Assessment of Prevalence, Indications, and Outcomes. (April 2022) - Kaye, Alison; Shah, Karina; Lybrand, Sandra; Baysinger, Sarah; Tracy, Meghan
Objective: To determine the prevalence of, reasons for, and outcomes related to Child Protective Services (CPS) referral in an isolated and syndromic cleft lip/palate population. Design: Retrospective cohort study. Setting: Tertiary Children's Hospital. Patients: Any patient <18 years of age attending the multidisciplinary cleft team for care at our institution with a history of referral to CPS by the cleft team during the study period 2009 to 2014. Main Outcome Measures: The number of children with CPS referrals, reasons for CPS referrals, outcomes of CPS referrals, associated psychosocial risk factors potentially predictive of CPS referral; demographics and cleft-related surgical history was also reviewed for each patient. Results: Of 1392 patients, 25 (1.8%) were identified with a history of referral to CPS. Average age at referral was 11 months; 76.0% of patients were <1 year of age. Most referrals (64.0%) were directly associated with issues related to cleft care. Identified psychosocial risk factors included financial strain, mental illness/cognitive disability, transportation issues, and inadequate social support. Nine families ultimately lost custody of their children temporarily (n = 5) or permanently (n = 4). Conclusions: Cleft team family referral to CPS involves long-term patient care challenges requiring maximal medical and social support. Families are most commonly referred for issues related to medical neglect, which can lead to failure to thrive, delays in care, and ultimate removal from the home. Identifying families with known psychosocial risk factors and providing increased support may potentially help avoid referrals to CPS.